2013
DOI: 10.1177/0363546513510391
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Primary Anterior Shoulder Dislocation Requiring Closed Reduction in Ontario, Canada

Abstract: Young male patients have the highest incidence of primary anterior shoulder dislocation requiring CR and the greatest risk of repeat shoulder CR. Patient, provider, and injury factors all influence repeat shoulder CR risk. A comprehensive understanding of the epidemiology of primary anterior shoulder dislocation will aid management decisions and injury prevention initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
178
3
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(207 citation statements)
references
References 47 publications
(121 reference statements)
13
178
3
6
Order By: Relevance
“…A recent population-based study by Leroux et al [8] reported a 20% incidence of recurrent instability following a first time anterior shoulder dislocation in all adult patients. The highest risk group was young (< 20 years), male patients with an incidence density ratio of 98 per 100000 person-years.…”
Section: Epidemiologymentioning
confidence: 99%
“…A recent population-based study by Leroux et al [8] reported a 20% incidence of recurrent instability following a first time anterior shoulder dislocation in all adult patients. The highest risk group was young (< 20 years), male patients with an incidence density ratio of 98 per 100000 person-years.…”
Section: Epidemiologymentioning
confidence: 99%
“…Results: The co-occurrence of injuries was high [odds ratio (OR) 5 11.47; 95% confidence interval (CI) A shoulder dislocation is a traumatic event with an incidence of around 24 per 100 000 in North America. 1,2 Anterior shoulder dislocation is the most common direction, and most patients are male. [1][2][3][4] The highest incidence (48 per 100 000) was found between the ages of 20 and 29 years.…”
mentioning
confidence: 99%
“…They found medical comorbidities, dislocation associated with humeral tuberosity fracture, and reduction performed by an orthopaedic surgeon to be protective for recurrent instability. 8 History of prior injury was a risk factor for future instability in a review of a young military population by Cameron et al 2 Specifically, patients with a selfreported history of glenohumeral instability were noted to be 5 times more likely to experience another instability event during the study time period.…”
Section: Discussionmentioning
confidence: 97%
“…There is still debate regarding the precise role of surgical treatment in this condition. While previous authors have analyzed risk factors for recurrent instability 2,8,15 and failure after shoulder stabilization surgery in this population, 1 there has been a lack of investigation regarding which variables are associated with surgery for shoulder instability in the first place. This study is novel in that it seeks to address this question in the framework of the FEDS classification system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation